Plant-based Complementary and alternative medicine used by breast cancer patients at the Hospital Universitario San Ignacio in Bogotá, Colombia. - Marcela Mercado; Luisa Benitez Cardenas; Susana Fiorentino; Luz Angela Diaz; Lilian Torregrosa (Universitas Scientiarum)
The present study estimates the frequency of the use of plant-based Complementary and Alternative Medicine (CAM) by breast cancer patients. From June to December of 2011, a self-administered questionnaire was given to 404 breast cancer patients receiving outpatient therapy at the Javeriana Oncology Center of the Hospital Universitario San Ignacio in Bogotá. The prevalence of patient CAM use was 57%, out of which 76% was based on plants like anamú, aloe, red fruits and soursop. Sixty-five percent of the patients had a positive perception of using medicinal plants and 57% used them simultaneously with the oncologist recommended allopathic treatment. We concluded that the frequency of CAM use in breast cancer patients at the Javeriana Oncology Center is within the prevalence range reported worldwide, despite differences in CAM types and frequencies. The high rates of plant-based CAM use without physician consent, brings about the lack of assessment of the synergic or antagonistic effects of CAM therapies on the allopathic treatment of breast cancer and evaluation of the antitumor and immunomodulatory potential of the traditionally used plants.